Mediasi Penal Sebagai Alternatif Penyelesaian Perkara Kecelakaan Lalu Lintas di POLRES Pasuruan - Eko Iskandar* (Airlangga Development Journal, 2017)
In  Pasuruan  Regional  police  station  amount  of  accidents  in  2018  has decreased, but amount of dead victims still relatively high. In 2018 there 533 events, in 2017 there 809 events and 2016 there 908 events, if on average there  756 events in the last 3 years. The majority of  settlement the case uses the mediation of penal process. So the authors interested in researching the basis of the implementation  of penal mediation  as an  alternative to  the settlement of cases in traffic accidents in Pasuruan Regional Police and the obstacles   the   implementation   of   traffic   accident   settlement   through mediation penalties. The method in this study uses a qualitative approach data collection techniques through interviews and documentation studies. Data  analysis techniques  based  on  data  collection,  data  reduction, data display    verification and confirmation of conclusions. The basis of implementation the mediation of   law, among others, legal basis and sociological basis The juridical basis used includes the authority to "act according to self-assessment" as regulated in Article 18 of Law Number 2 of 2002. While the sociological basis includes the perpetrators and victims alike agreeing to make peace; In the event the offender is not entirely guilty; The impactor is  willing  to  provide compensation  of money and medical expenses to the victim; and the immature age of the traffic accident perpetrators. Barriers to the implementation the mediation of penalties include conflicts with penal system that applies in UULLAJ. The second obstacle the conflict between the interests of the perpetrators and victims, in this case between the wishes of the victims who sometimes expect high compensation or there are several parties from victims who do not agree with each other. The next obstacle is the existence of a clash in the value of legal certainty where compensation will basically not stop the accident case process.